2011
DOI: 10.1159/000330234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Sugar-Free Chewing Gum Containing Magnolia Bark Extract on Different Variables Related to Caries and Gingivitis: A Randomized Controlled Intervention Trial

Abstract: The effect of magnolia bark extract (MBE) on different variables related to caries and gingivitis administered daily through a sugar-free chewing gum was evaluated. The study was performed with healthy adult volunteers at high risk for caries as a randomized double-blind interventional study. 120 subjects with a salivary mutans streptococci (MS) concentration ≧105 CFU/ml and presence of bleeding on probing >25% were enrolled and divided into three groups: magnolia, xylitol and control. The study des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 48 publications
0
49
0
Order By: Relevance
“…The use of plant extracts is becoming quite popular in caries prevention strategies [Kim and Kinghorn, 2002;Campus et al, 2011]. The present study was aimed to evaluate the effect of the 2 extracts from S. rebaudiana , stevioside and rebaudioside A, on in vitro S. mutans biofilm growth and on plaque pH in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The use of plant extracts is becoming quite popular in caries prevention strategies [Kim and Kinghorn, 2002;Campus et al, 2011]. The present study was aimed to evaluate the effect of the 2 extracts from S. rebaudiana , stevioside and rebaudioside A, on in vitro S. mutans biofilm growth and on plaque pH in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled intervention trial (Campus et al 2011) revealed that healthy adult individuals who chewed xylitol gum had a significantly lower concentration of salivary Streptococcus mutans compared to baseline. A systematic review of the literature suggested that the use of xylitol chewing gum as an adjunct to tooth brushing provided a beneficial reduction in plaque scores in a systematic review (Keukenmeester et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of antidiabetes are still unclear for Magnolia constituents. Therefore, ME are not used in antidiabetic clinical trial, though, clinical trials have demonstrated that ME may be important medicines for treating a variety of conditions such as menopause [53], anxiety [54], and gingivitis [55]. Now, it is necessary that we identify the bioactive constituents of ME, and delineate possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%